Kink-excitation of N-system under spatio-temporal noise - Bakanas, R. (Nonlinear Analysis: Modelling and Control, 1998)
Random walk of the nonlinear localized excitations in a dissipative N-system, i.e., the influence of the irregular perturbations on the kink-shaped excitations in a system characterized by nonlinearities of "N-type", is analyzed. The “evolution” of the randomly walking excitation is described by the onedimensional PDE (partial differential equation) of the parabolic type. The analysis of the considered excitations is performed for the case of the disturbing torque which is randomly distributed in space and time, and makes up the white Gaussian noise. An iterative scheme of perturbation technique is presented to derive the randomly perturbed solutions of the considered evolution equation in a general case of N-system. The average characteristics of the “steady state” of the randomly walking kink-excitations are examined in detail. The explicit expressions that describe the considered random walk are presented for the particular case of the kink-shaped excitations of the free electron gas in semiconductors.
Keywords: none